Effect of jointed dry board and overlapped profiled steel sheet in PSSDB walling unit with door opening / Mohd Rashid Ya'acob (Faculty of Civil Engineering, 2003)
The report presents a load bearing wall system using Profiled Steel Sheet Dry Board (PSSDB) with door opening and jointed dry board and overlapped Profiled Steel Sheet. The PSSDB system wall carry axial, out-of-plane bending and in-plane shear loads. To restrain these failures, the critical limit from experiment and theory will be determined as lateral deflection ultimate load capacity, stress strain pattern and cracking and failure response. Three specimens of panel are prepared and tested under axial load, overlapped and jointed condition. The overall dimension of each specimen is 1320 x 1000 mm and door opening 700 x 300 mm. This experiment was used Bondek II as profiled steel sheet and Cemboard as two skins dry board. The average ultimate load capacity for this studied was 328 kN and average maximum lateral displacement was 5.98 mm. The specimens tend to fail at both combination flexural on top section and buckling at side of panels.